2013
DOI: 10.1002/elan.201300304
|View full text |Cite
|
Sign up to set email alerts
|

FullereneβCyclodextrin Conjugate Based Electrochemical Sensing Device for Ultrasensitive Detection of p‐Nitrophenol

Abstract: The article describes the use of a fullerene (C 60 )-b-cyclodextrin conjugate, synthesized via 1,3-dipolar cycloaddition, for the ultrasensitive electrochemical detection of p-nitrophenol. This conjugate was successfully immobilized on the surface of a glassy carbon electrode and the developed device showed high activity towards p-nitrophenol due to the synergetic effect of C 60 , the latter becoming highly conductive upon reduction. The determination of p-nitrophenol was performed by using square wave voltamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A variety of nanomaterials such as α‐MnO 2 nanotubes , codoped Mn 2 O 3 ‐ZnO nanoparticles nanoporous gold films , CoO x nanostructures , Co 3 O 4 nanostructures , ZnO microstructures , copper oxide nanoparticles , nano gold , copper nanoparticles , multi‐walled carbon nanotubes , single walled carbon nanotubes , SWCNT/pyrenecycodextrin nanohybrids , chitosan/phenyltrimethoxysilane/AuNPs hybrid films , fullerene‐β‐cyclodextrin cojugates , hybrid inorganic‐organic coating based on prussian blue and polyazulene derivatives have been employed to modify glassy carbon or metal electrodes for the electrochemical detection of p‐NP.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of nanomaterials such as α‐MnO 2 nanotubes , codoped Mn 2 O 3 ‐ZnO nanoparticles nanoporous gold films , CoO x nanostructures , Co 3 O 4 nanostructures , ZnO microstructures , copper oxide nanoparticles , nano gold , copper nanoparticles , multi‐walled carbon nanotubes , single walled carbon nanotubes , SWCNT/pyrenecycodextrin nanohybrids , chitosan/phenyltrimethoxysilane/AuNPs hybrid films , fullerene‐β‐cyclodextrin cojugates , hybrid inorganic‐organic coating based on prussian blue and polyazulene derivatives have been employed to modify glassy carbon or metal electrodes for the electrochemical detection of p‐NP.…”
Section: Introductionmentioning
confidence: 99%
“…Several interesting studies on the oxidation and reduction of 4-NP have been reported using various fabricated electrodes such as glassy carbon electrode (GCE), graphene, carbon nanotubes (CNTs), ordered mesoporous carbons, fullerene-b-cyclodextrin, poly(methylene blue), silver nanoparticles, and nano porous gold. 10,11,[13][14][15][16][17][18][19][20][21][22][23] Nonetheless, a majority of research work is focusing on electrocatalytic activity of electrode materials rather than the sensitivity and selectivity of 4-NP detection.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction peak current of pÀ NP exhibited linear proportionality to the square root of scan rate of 20-100 mVs À 1 with a linear regression equation I pc (μA) = 0.1153 p ν + 4.3616 (R 2 = 0.9937) (Figure 5b) suggesting that the reduction of pÀ NP at NiOÀ NPs-α-CD-rGO-GCE was a diffusion controlled process [69].For fully irreversible electron transfer process the Randles-Sevcik equation [70] is Scheme 2. Mechanism of electrochemical reduction of pÀ NP to p-AP via p-(hydroxyamino)phenol (p-HAP) and p-QI intermediates and oxidation of electrogenerated p-AP to p-QI at NiOÀ NPs-α-CD-rGO-GCE [34,66].…”
Section: Kinetics Of the Electrode Reactionmentioning
confidence: 99%